2021
DOI: 10.1017/s1479262121000095
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characterization and genotypic identity of African yam bean (Sphenostylis stenocarpaHochst ex. A. Rich. Harms) germplasm from diverse ecological zones

Abstract: African yam bean (AYB) is an affordable protein source capable of diversifying the food base in sub-Saharan Africa. However, research efforts made towards the crop's improvement and in expanding production are limited. This study characterized 169 AYB accessions at Jimma, Ethiopia, using 31 phenotypic characters. The analysis of variance revealed highly significant (P < 0.01) differences for days to 50% flowering, days to first flowering, leaf area, number of seeds per pod, pod length, seed thickness, total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…e 93 accessions were morphologically characterized [36]. e physical properties of the accessions used in the present study are shown in Supplementary Table 1.…”
Section: Genetic Materialsmentioning
confidence: 99%
“…e 93 accessions were morphologically characterized [36]. e physical properties of the accessions used in the present study are shown in Supplementary Table 1.…”
Section: Genetic Materialsmentioning
confidence: 99%
“…Nevertheless, the food potential of the crop remains widely untapped, which can be attributed to several constraints such as long cooking hours of up to 24 hours [41][42][43][44], a long-maturity cycle of 9-10 months [16,17,45], and the abundance of anti-nutrition factors [35,[46][47][48][49]. However, the genetic variability reported in the crop [9,[50][51][52][53] provides a foundation for breeders to develop improved cultivars. In particular, the availability of AYB cultivars with reduced cooking time could boost the cultivation and consumption of the crop.…”
Section: African Yam Beanmentioning
confidence: 99%
“…Table 1 presents the physical properties reported in AYB seeds. AYB seeds are, dicot in nature and they can measure up to 10 mm in length and 7 mm in width and thickness [9,[50][51][52][53]56]. The seeds of AYB differ in texture across germplasm; they could be rough, wrinkled, or smooth.…”
Section: Structure Of African Yam Bean Seedsmentioning
confidence: 99%
“…The nitrogen-fixing ability of legumes holds a significant value for smallholder farms in SSA, characterized by nutrient-deficient and degraded soils (Kamanga et al 2014 ; Kimutai et al 2023 ; Ndlovu et al 2022 ), especially considering the limited use of inorganic fertilizers due to their high prices. In addition to their agroecological benefits, legumes are an important nutrient-dense food staple item and are considered beneficial for both human health and the health of the planet (Aiking 2011 ; Foyer et al 2016 ; Kumar and Pandey 2020 ; Shitta et al 2021 ; Stagnari et al 2017 ). Legumes are high in protein, important minerals (P, Ca, K, Mg, Fe, Zn, Cu, Mn, and Se), vitamins (B1, B2, B3, B5, B6, choline, E, and folate), and fiber contents (Ojiewo et al 2015 ; Snapp et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%